The Factors Affecting the Production of Manufacturing Industry in Palestine - الكحلوت هشام عبد الكريم إبراهيم (Finance and Business Economies Review, 2021)
This study aimed at identifying the most important factors that affect the production of manufacturing industry in Palestine by conducting a test on the impact of industrial exports, inflation, foreign direct investment, grants and foreign aid, as well as the production of manufacturing industry in Palestine. The descriptive-analytical methodology was used by relying on standard methods to study the factors affecting the production of the manufacturing industry in Palestine. Secondary sources were relied on to collect data by relying on a desk survey of literature related to the research topic as those sources included books, periodicals, published studies and reports that were issued by official authorities to collect data on the study variables. The study community has represented the establishments operating in the manufacturing industries sector in the Palestinian territories. The factors affecting the production of manufacturing industry in Palestine were studied by using the time series during for the period (1996-2018). It relied on modern methods in studying the factors affecting the production of manufacturing industry in Palestine and identifying their statistical characteristics through the use of time series analysis method and the joint integration of Johansson. The model of this study was also estimated through the ordinary Least Squares method (OLS). It concluded a set of important results that were represented in the presence of a positive moral effect of statistical significance for industrial exports on the Production of Manufacturing Industry in Palestine, which is related to the role these exports play in providing foreign currencies to the country and enabling investors in the manufacturing sector to achieve a steady capital expansion as a result to maximize the profitability rates associated with exporting. In addition to the presence of a negative impact with a significance for the rate of inflation in the Production of Manufacturing Industry in Palestine. finally, the results also showed that there was no statistically significant effect for both grants, foreign aid and investment Direct foreign production in the manufacturing industry in Palestine. The study recommended the necessity for the Palestinian National Authority to provide the necessary infrastructure to facilitate the work of the manufacturing sector to enhance its ability to expand production. This is can be done by focusing on establishing well-prepared border industrial zones. Besides, the establishment of industrial zones within the municipalities borders to gather the scattered factories within Residential neighborhoods in Palestine.